EFFECTIVENESS OF TRUNK TRAINING EXERCISES VERSUS SWISS BALL EXERCISES FOR IMPROVING SITTING BALANCE AND GAIT PARAMETERS IN ACUTE STROKE SUBJECTS (International Journal of Physiotherapy, 2015)
Background: The aim of this study is to evaluate the effectiveness of trunk training and Swiss ball exercises in acute stroke subjects. Trunk is often neglected part in the stroke rehabilitation, trunk training exercises and Swiss ball exercises result in better recruitment of trunk muscles thus improving sitting balance and gait parameters in acute stroke subjects. However literature evidences for trunk training exercises and Swiss ball exercises in improving sitting balance and gait are scarce in acute stroke population.Methods: A total of 60 subjects who met the inclusion criteria were recruited from department of physiotherapy, G.S.L general hospital and were randomly allocated into 2 groups with 30 subjects in each group. Initially all of them were screened for balance and gait using trunk impairment scale and by assessing gait parameters, after that they were given a 30min of trunk training and Swiss ball exercises for 5 days a week for 4 weeks. Both the groups received conventional physiotherapy for 4 weeks.Results: Post intervention there was no significant difference between the two groups. There was improvement post treatment in trunk training group (P